El “gran cisma fenomenológico” y el “cisma fenomenológico-existencial”. Sobre la continuidad en la crítica contemporánea respecto del tránsito de Husserl hacia el idealismo trascendental - Heffernan, George (2016)
It is generally acknowledged that there were two schisms in the early historyof the phenomenological movement. The first, the Great Phenomenological Schism, started between 1905 and 1913, as many of his younger contemporaries, for example Pfänder, Scheler, Reinach, Stein, and Ingarden, rejected Husserl’s transformation of phenomenology from the descriptive psychology of the Logical Investigations (1900/19011) into the transcendental idealism of Ideas I (1913). The second, the Phenomenological-Existential Schism, happened between 1927 and 1933, as it emerged that with Being and Time (1927) Heidegger’s philosophy had moved away from Husserl’s transcendental phenomenology of consciousness toward an ontological analytic of human existence as the way to an interpretation of the question of the meaning of Being. This paper is about neither the first schism per se nor the second schism per se but about the relationship between the two. It suggests that the first schism anticipated the second and the second recapitulated the first, so that, although the first could have occurred without the second, the second would not have happened as it did without the first. It also indicates that the second schism lies temporally much closer to the first schism than has been hitherto appreciated. Above all, the paper seeks an answer to this question: How do the Great Phenomenological Schism and the Phenomenological-Existential Schism illuminate one another philosophically?